The challenges and prospects of heritage sites in ethiopia in case of tirusina mosque - Mehadi, MuhamedAwal (International research journal of management, IT and social sciences, 2020)
In this paper, the researchers will briefly examine the pitfalls of tourism development in the Amhara region taking the Tirusina mosque as a heritage site as a case. Ethiopia is a country with untapped tourism potential. Despite the immense opportunities that exist in Ethiopia in terms of both cultural and natural resources for tourism development, the country continues to lag behind other economies in the region in terms of tourism growth and development. Besides the lack of society’s presumption about the important of tourism for the development of the country’s economy, no more work was done to improve and increase the flow of tourist arrivals for the reason that our country has strong potential as a tourism destination offering a rich array of cultural, historic and natural sites that set it apart from its neighbors. This helps to investigate and document the tourism sites of the region under study. The researcher will conclude by presenting a series of challenges for those involved in developing the tourism sectors to enhance the development of the country’s economic base.